A novel technique for biobanking of large sections of radical prostatectomy specimens. Issue 3 (21st November 2017) - Lindh, Claes; Delahunt, Brett; Samaratunga, Hemamali; Yaxley, John; Gudjónsdóttir, Jóna; Clements, Mark; Lindberg, Johan; Egevad, Lars
Abstract : Aims: Harvesting of unfixed tissue from radical prostatectomy specimens for research purposes is challenging. Many prostate cancers cannot be identified at gross inspection, and this tumour is notoriously multifocal and heterogeneous. We aimed to develop a technique to allow detailed topographic analysis and the sampling of a sufficient amount of tumour without jeopardising clinical reporting. Methods and results: A custom‐made double‐bladed knife was utilised for cutting a 4‐mm‐thick horizontal section of the prostate. The slices were split into segments that were frozen in gel, cryosections were cut, and RNA integrity numbers (RINs) were analysed. Sections were cut from all blocks of 20 cases, and the cutting time was monitored. Slides were scanned, and the slices were digitally reconstructed. Cutting frozen sections of an entire slice took 79–253 min (mean 162 min). Tumour was detected in frozen sections of 85% (17/20) of cases and in 46% (72/155) of blocks. The morphological quality was determined to be excellent, and RIN values were high (mean 8.9). Conclusions: This novel protocol for biobanking of fresh tissue from prostatectomy specimens provides sufficient tumour material for research purposes, while also enabling reporting of histopathology. The harvesting of a full tissue slice facilitates studies of tumour multifocality and heterogeneity.